2006
DOI: 10.1124/jpet.105.095067
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Electrophysiological Characterization of Store-Operated Currents and Capacitative Ca2+Entry in Vascular Smooth Muscle Cells

Abstract: Capacitative Ca2ϩ entry (CCE) in vascular smooth muscle cells contributes to vasoconstrictor and mitogenic effects of vasoactive hormones. In A7r5 rat aortic smooth muscle cells, measurements of cytosolic free Ca 2ϩ concentration ([Ca 2ϩ ] i ) have demonstrated that depletion of intracellular Ca 2ϩ stores activates CCE. However, there is disagreement in published studies regarding the regulation of this mechanism by the vasoconstrictor hormone [Arg 8 ]-vasopressin (AVP). We have employed electrophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 50 publications
4
58
1
Order By: Relevance
“…A7r5 vascular smooth muscle cells, although their relative roles may differ under different conditions [4][5][6][7][8][9], influenced by both the pattern of expression of TrpC proteins [7,10] and the nature of the stimulus [7]. It is, however, clear that in A7r5 cells, as in many other cells [11][12][13], arachidonic acid (AA) contributes to the coordinate regulation of CCE and NCCE [5,6,14].…”
Section: -Vasopressin (Avp) Inmentioning
confidence: 99%
“…A7r5 vascular smooth muscle cells, although their relative roles may differ under different conditions [4][5][6][7][8][9], influenced by both the pattern of expression of TrpC proteins [7,10] and the nature of the stimulus [7]. It is, however, clear that in A7r5 cells, as in many other cells [11][12][13], arachidonic acid (AA) contributes to the coordinate regulation of CCE and NCCE [5,6,14].…”
Section: -Vasopressin (Avp) Inmentioning
confidence: 99%
“…As a negative control, we also visualized TRPC6 non-selective cation channels, which are known to be expressed in MASMCs (33), but, as an ion channel of a different class, would not be expected to physically interact with Kv7 channel subunits. Kv7.4, Kv7.5, and TRPC6 could each be visualized individually in MASMCs (Fig.…”
Section: Detection Of Heteromeric Kv74/75 Channels In Masmcs-mentioning
confidence: 99%
“…Over-expression of the human trpc1 gene in rat pulmonary artery enhanced vasoconstriction via store depletion-mediated Ca 2+ influx [33]. One study found that thapsigargin-stimulated store-operated current was reduced in TRPC1 siRNA-or TRPC1 antisense-expressing cells [34]. Ahmmed et al [35] demonstrated that phosphorylation of TRPC1 via PKC alpha was an important determinant of store-operated Ca 2+ entry in human ECs.…”
Section: Trp Channels Participate In Vasoconstrictionmentioning
confidence: 99%